OWNERSHIP CONCENTRATION AND FIRM PERFORMANCE: AN EMPIRICAL ANALYSIS IN OMAN - Al Ani, Mawih Kareem; Al Kathiri, Asma Mohammed (The European Journal of Applied Economics, 2019)
This study investigates the effect of ownership concentrations on firm performance. A sample of 115 Omani companies in three sectors (i.e. financial, industrial and service) was selected for the study. The sample companies selected were listed in the Muscat Securities Market for a period of five years (2011–2015). Four types of ownership were analysed, namely, the ownership of Omani investors, the Gulf Cooperation Council (GCC) country investors, Arab non-GCC investors, and foreign investors. Firm performance was measured by return on assets (ROA), return on equity (ROE), and market fair value (MFV) of share. Panel regression was used to study the effect of ownership concentrations on firm performance. Results reveal a positive and significant effect of GCC countries and foreign investors on ROA only in the industrial sector. Moreover, a positive and significant effect of Omani and GCC countries investors was found on MFV in the service sector. Finally, results found no effect of ownership concentrations on ROE in all sectors.